“Speaking as one African to another”: friendship as politics in the letters of Robert Sobukwe and Benjamin Pogrund, 1960-1969 - Daitz, Emma F (Department of Sociology, 2025)
This dissertation draws on the correspondence exchanged between Robert Sobukwe, one of the founders of the Pan Africanist Congress (PAC), and Benjamin Pogrund, a journalist at the Rand Daily Mail and a member of the Liberal Party of South Africa, to argue that friendship constitutes a form of politics. Through a close examination of the Sobukwe-Pogrund letters, read against the historical context of their production, the dissertation charts the ways in which these two friends refused the racial essentialism of the apartheid state through gestures of care, reciprocity, and other-directedness. Though not speaking in the oppositional register of anti-colonial or anti-apartheid nationalist struggle, I argue that this refusal, and the many actions which brought it into being, constitutes a form of politics that demands attention and analysis in times of racial polarizations and antagonisms. The letters upon which my analysis is based were written between 1960 and 1969. 1960 was the year of the PACs anti-pass campaign to which the state responded by killing 69 people and seriously wounding 180 in the Sharpeville Massacre. The letters, written during Sobukwe's subsequent imprisonment, were donated by Benjamin Pogrund in the early 1990s to the Wits Historical Research Papers archive at the University of the Witwatersrand in Johannesburg and were subsequently digitized and made available online. In addition to the letters, I also draw on a collection of public speeches made by Sobukwe in the late 1950s to 1960. My analysis draws on insights from the fields of postcolonial and African studies. Consulting Sobukwe's public speeches, I argue that his openness to Pogrund was not an idiosyncrasy but indeed embedded within his Pan-Africanist political commitments as evidenced by his open-ended theorisation of the category of the African in a post-apartheid future (that is yet to come) thereby establishing an anti-racist lineage for non-racialism. Throughout the dissertation, I attempt to hold a series of contradictions or paradoxes together as part of an ethical commitment to face the complexities of raced being and belonging in everyday life that both recognises and opposes racism and, at the same time, is alert and responsive to the fact that even in conditions of racist oppression forms of identity, relationality, and mutuality emerge between people which may facilitate life-affirming political and social possibilities.